U.S. Foreign Policy for a Post-War Recovery Program.: hearings before the United States House Committee on Foreign Affairs, Eightieth Congress, first session and Eightieth Congress, second session. - United States. (U.S. G.P.O., 1948)
Considers (80) H.R. 4840, (80) H.R. 4579
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part V
Considers (80) H.R. 4840, (80) H.R. 4579
Keywords: Reconstruction (1939-1951) / Law and legislation / United States.; Economic assistance, American / Law and legislation.